Pengembangan Bahan Ajar Tahsin Metode Maffaz Berbasis Mind Mapping dan Pendidikan Dasar Al-Quran di Pondok Pesantren - Delaardilasofia (Lisan An Nathiq : Jurnal Bahasa dan Pendidikan Bahasa Arab, 2026)
This study aims to develop Tahsin teaching materials using the Maffaz Method based on Mind Mapping at Pesantren Tahfidz Maskanul Huffadz Bintaro, South Tangerang. The study is motivated by the lack of engaging and interactive teaching materials, which affects students’ motivation and understanding in learning Tahsin. This research employs a Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The results indicate that the developed teaching materials are highly feasible, with student response reaching 91% and teacher response 92%, categorized as “very feasible.” The effectiveness test using a paired sample t-test shows a correlation value of 0.712 with a significance level of < 0.001, indicating a significant improvement in learning outcomes after using the materials. Therefore, the Mind Mapping-based Tahsin teaching materials are considered both feasible and effective in enhancing students’ understanding and learning outcomes.